Lipase Processing of Complex Lipid Antigens. Issue 9 (22nd September 2016) - Sander, Peter; Becker, Katja; Molin, Michael Dal
Abstract : Mycobacterium tuberculosis synthesizes a wide variety of complex lipids that can serve as antigens in immune recognition of the bacterium. In this issue of Cell Chemical Biology, Gilleron et al. (2016) identify key enzymes essential for lipid antigen processing, which is required for CD1b-restricted T cell activation. Abstract : Mycobacterium tuberculosis synthesizes a wide variety of complex lipids that can serve as antigens in immune recognition of the bacterium. In this issue of Cell Chemical Biology, Gilleron et al. (2016) identify key enzymes essential for lipid antigen processing, which is required for CD1b-restricted T cell activation.